Rhytidosteid temnospondyls in Gondwana: A new taxon from the Lower Triassic of Brazil - Dias da Silva, Sergio (2006)
A new South American Early Triassic stereospondyl is described and considered to represent a new taxon, Cabralia lavinai gen. et sp. nov. The material consists of two well-preserved skull fragments. According to recent phylogenetic analyses of rhytidosteids and related taxa, the new taxon is referred to the Rhytidosteidae based on the presence of orbits that are located close to the skull margins, an otic notch that is reduced to an embayment, tabular horns that are reduced and broad based, a straight posterior margin of the palate, skull sculpture with nodules and pustules, and a 'twisted' quadrate ramus of the pterygoid. The presence of a prominent lacrimal bone suggests a basal position within Rhytidosteidae for C. lavinai, and possibly a close relationship with the Indian Indobrachyops, because all other known rhytidosteids exhibit the derived condition of an absence of the lacrimal. The presence of a basal rhytidosteid in the Paraná Basin of South America strongly supports previous hypotheses of a Gondwanan origin and radiation of stereospondyl temnospondyls during the Early Triassic, but leaves unresolved the question of where exactly they arose within that region.